Employment status and occupational level of adult survivors of childhood cancer in Great Britain: The British childhood cancer survivor study. Issue 12 (7th April 2017) - Frobisher, Clare; Lancashire, Emma R; Jenkinson, Helen; Winter, David L; Kelly, Julie; Reulen, Raoul C; Hawkins, Michael M; ,
Abstract : The British Childhood Cancer Survivor Study (BCCSS) provides the first detailed investigation of employment and occupation to be undertaken in a large population‐based cohort. Previous studies have been limited by design issues such as using small numbers of survivors with specific diagnoses, and involved limited assessment of employment status and occupational level. The BCCSS includes 17, 981 5‐year survivors of childhood cancer. Employment status and occupational level were ascertained by questionnaire from eligible survivors ( n = 14, 836). Multivariate logistic regression was used to explore factors associated with employment and occupation, and to compare survivors to their demographic peers in the general population. Employment status was available for 10, 257 survivors. Gender, current age, cancer type, radiotherapy, age at diagnosis and epilepsy were consistently associated with being: employed; unable to work; in managerial or non‐manual occupations. Overall, survivors were less likely to be working than expected (OR (99% CI): 0.89 (0.81–0.98)), and this deficit was greatest for irradiated CNS neoplasm survivors (0.34 (0.28–0.41)). Compared to the general population, survivors were fivefold more likely to be unable to work due to illness/disability; the excess was 15‐fold among CNS neoplasm survivors treated with radiotherapy. Overall survivors were less likely to be in managerial occupations than expected (0.85 (0.77–0.94)). However, bone sarcoma survivors were more likely to be in these occupations than expected (1.37 (1.01–1.85)) and also similarly for non‐manual occupations (1.90 (1.37–2.62)). Survivors of retinoblastoma (1.55 (1.20–2.01)) and 'other' neoplasm group (1.62 (1.30–2.03)) were also more likely to be in non‐manual occupations than expected. Abstract : What's new? Employment and job satisfaction contribute to individual wellbeing and performance in modern society. For survivors of childhood cancer, however, poor health can significantly hinder the ability to work, the present study suggests. Using data from the British Childhood Cancer Survivor Study, the authors show that compared with the general population, survivors of childhood cancer were less likely to be working, with work activity limited particularly by illness and disability. Impacts were greatest for survivors of central nervous system neoplasms treated by radiotherapy. The findings help identify factors that could be targeted to maximize survivors' employment potential.